2017
DOI: 10.1093/gerona/glx027
|View full text |Cite
|
Sign up to set email alerts
|

Four Genome-Wide Association Studies Identify New Extreme Longevity Variants

Abstract: The search for the genetic determinants of extreme human longevity has been challenged by the phenotype's rarity and its nonspecific definition by investigators. To address these issues, we established a consortium of four studies of extreme longevity that contributed 2,070 individuals who survived to the oldest one percentile of survival for the 1900 U.S. birth year cohort. We conducted various analyses to discover longevity-associated variants (LAV) and characterized those LAVs that differentiate survival to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 46 publications
2
91
0
1
Order By: Relevance
“…In fact, a focused meta-analysis of 4 studies of centenarians reported in [24] showed replication of a large number of the longevity variants in [18] when the studies used a consistent and select enough definition of longevity. Similarly, in a recent meta-analysis of 4 genome-wide association studies with more than 6,000 controls and of 2,086 very old individuals (age range 95–119), in which extreme longevity was defined as surviving to or beyond the oldest 1% of individuals from the 1900 birth year cohort, we identified 37 SNPs in chromosomes 7, 12, and 19 that reached genome wide significance (p < 5E-8) ([25], under review).…”
Section: Meta-analyses Of Genome-wide Association Studies Of Longevitymentioning
confidence: 65%
“…In fact, a focused meta-analysis of 4 studies of centenarians reported in [24] showed replication of a large number of the longevity variants in [18] when the studies used a consistent and select enough definition of longevity. Similarly, in a recent meta-analysis of 4 genome-wide association studies with more than 6,000 controls and of 2,086 very old individuals (age range 95–119), in which extreme longevity was defined as surviving to or beyond the oldest 1% of individuals from the 1900 birth year cohort, we identified 37 SNPs in chromosomes 7, 12, and 19 that reached genome wide significance (p < 5E-8) ([25], under review).…”
Section: Meta-analyses Of Genome-wide Association Studies Of Longevitymentioning
confidence: 65%
“…Humans exhibit substantial variation in longevity and healthspan, including the development of frailty and physical impairment in old age . Moreover, only a subset of AD patients exhibit motor‐related impairments .…”
Section: Discussionmentioning
confidence: 99%
“…As with long-term memory, some strains exhibit resilience to age-related and/or AD-related impairments, exhibiting little decline with age, regardless of genotype. In contrast, some strains even showed improvement with age, suggesting modifier genes exist that influence Humans exhibit substantial variation in longevity and healthspan, [30][31][32] including the development of frailty and physical impairment in old age. 27 Moreover, only a subset of AD patients exhibit motor-related impairments.…”
Section: Influence Of Genetic Background On Sensorimotor Traits Andmentioning
confidence: 99%
“…Identifying longevity loci is important because these loci likely represent key mechanisms of a life-long decreased Mortality 15, 16 , decreased morbidity 9, 12, 18 and compression of morbidity towards the end of the lifespan 1921 . Currently, genome wide linkage and association studies (GWAS) identified a limited number of loci promoting longevity 2231 , for example the APOE and F0X03A genes (more details can be found in current review papers 22, 23, 30 ). However, many of the identified loci could not be replicated in independent studies as yet.…”
Section: Mainmentioning
confidence: 99%
“…As the definition of heritable longevity was not yet established, the construction and application of the family selection scores have not yet been adopted as state of the art in longevity research. As such, the majority of genealogical 5, 6, 10–14, 45 and genetic studies 2426, 3134 focus only on single, and thus including sporadic, long-lived individuals (singletons), with some exceptions focusing for example on parental age 28, 29 or multiple siblings 7, 25 . In previous work, we showed that longevity defined as top 10% survivors or more extreme is transmitted to subsequent generations 16 .…”
Section: Mainmentioning
confidence: 99%